Stretching DNA by electric field and flow field in microfluidic devices: An experimental validation to the devices designed with computer simulations - Lee, Cheng-Han (American Institute of Physics, 2013)
We examined the performance of three microfluidic devices for stretching DNA. The first device is a microchannel with a contraction, and the remaining two are the modifications to the first. The modified designs were made with the help of computer simulations [C. C. Hsieh and T. H. Lin, Biomicrofluidics 5(4), 044106 (2011) and C. C. Hsieh, T. H. Lin, and C. D. Huang, Biomicrofluidics 6, 044105 (2012)] and they were optimized for operating with electric field. In our experiments, we first used DC electric field to stretch DNA. However, the experimental results were not even in qualitative agreement with our simulations. More detailed investigation revealed that DNA molecules adopt a globular conformation in high DC field and therefore become more difficult to stretch. Owing to the similarity between flow field and electric field, we turned to use flow field to stretch DNA with the same devices. The evolution patterns of DNA conformation in flow field were found qualitatively the same as our prediction based on electric field. We analyzed the maximum values, the evolution and the distributions of DNA extension at different Deborah number in each device. We found that the shear and the hydrodynamic interaction have significant influence on the performance of the devices.